3D Printing for fashion: new paradigms of design and consumption (ModaPalavra e-periódico, 2020)
This work aimed to take an approach on 3D printingtechnology in the fashion system, and the importance ofpostponement strategies, which are leading to greaterinformation sharing in the production chain of this sector. Itis also mentionate a way to introduce mass customizationbased on digital networks and other emerging technologiesthat has been breaking the traditional B2C (business toconsumer) paradigm. This study features three entry-levelmachinery design projects, non-industrial 3D printers, andissues related to new ways of consumption. It can beconcluded that 3D printing manufacturing is associated withlean production with few material surpluses or scraps, butwhen it comes to buying and shipping the product theseissues still seem not to be considered.
Keywords: 3D printing; fashion; consumption